2010
DOI: 10.1111/j.1749-771x.2010.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Voiding disorders among children and adolescents: surveillance after ‘voiding school’ treatment

Abstract: The purpose of this study was to evaluate children's lower urinary tract symptoms (LUTS) and health‐related quality of life (HR‐QoL) 1–6 years after treatment at voiding school. One to six years after the end of treatment for non‐neurogenic voiding disorders, 108 children were contacted (36% girls, current age 8–18 years). The study was conducted in two parts: data were retrospectively collected from the (i) children's medical records to determine their symptoms at the first consultation and (ii) children's cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…This reflects previous reports on how 'bothersome' managing a bladder condition can be (Mattsson et al, 2010). Conversely, the study by Mohn et al (2010) reported no correlation between Health related QoL (HR-QoL) and LUT symptoms, although a conclusion from their study was the need to ask young people before intervention about their psychosocial well-being. In our project, over half (55%, n = 36) of the children and young people reported sometimes, often or always missing out on social activities as a result of their bladder problems.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This reflects previous reports on how 'bothersome' managing a bladder condition can be (Mattsson et al, 2010). Conversely, the study by Mohn et al (2010) reported no correlation between Health related QoL (HR-QoL) and LUT symptoms, although a conclusion from their study was the need to ask young people before intervention about their psychosocial well-being. In our project, over half (55%, n = 36) of the children and young people reported sometimes, often or always missing out on social activities as a result of their bladder problems.…”
Section: Discussionsupporting
confidence: 72%
“…Nurse-led bladder assessment and training clinics or voiding schools have developed over the last decade in many areas including the USA, Europe and the UK and often involve education, biofeedback and behavioural management approaches (Rhodes, 2000;Mattsson et al, 2010;Mohn et al, 2010). There has been limited evaluation or appraisal of the efficacy and patient reported experience of these clinics, with studies predominantly focusing on functional outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation